Natural Gas - the Friendliest Fossil Fuel for Combating Climate Change and a Key to Sino-Russian Cooperation - PAUL CALANTER (Global Economic Observer)
Natural gas is the fossil fuel that is the most friendly for the environment, because is less polluting and more efficient than other conventional fuels. Although it is not as clean as wind or solar energy, the natural gas is considered a key energy source as the world moves towards a cleaner future. In this context, and also taking into account the current economic outlook, Russia and China have developed the "Power of Siberia" pipeline. The new pipeline is the largest gas infrastructure in Russia and one of the most important successes in the relationship between the two major powers. However, the relationship between Moscow and Beijing is not as strong as it seems at first glance. China, whose economy is eight times that Russia's and increasingly technologically advanced, is the main partner of this tandem, and Russia must accept its subordinate role. The main objective of the paper is assessing the importance of the “Power of Siberia” pipeline for the Sino-Russian economic cooperation. The methodology used is mainly qualitative, based on consulting the literature, studies and articles published by established specialists.